Cinematography : theory and practice : image making for cinematographers and directors - Brown, Blain (Focal Press, 2012)
There's more to being a DP than holding a light meter! With this book as your guide, you are on your way to learning not only about the equipment and technology, but also about the concepts and thought processes that will enable you to shoot professionally, efficiently, and with artistic mastery. A leading book in the field, Cinematography has been translated into many languages and is a staple at the world's top film schools. Lavishly produced and illustrated, it covers the entire range of the profession. The book is not just a comprehensive guide to current professional practice; it goes bey.